Problems of criminal law due to the scientific and technical revolution in the works of professor I. I. Gorelik - Savenok, Anatoly L. (Journal of the Belarusian State University. Law, 2021)
The scientific work of doctor of law, professor I. I. Gorelik about the impact of the scientific and technological revolution on the state and dynamics of crime is investigated. It is noted that the ideas put forward by him over the years have not lost their relevance, but, on the contrary, have received a new impetus in modern research. The formulated scientific provisions make it possible to comprehend in a new way the modern legal reality and propose ways to further improve the criminal legislation.